Molecular mapping of greenbug (Schizaphis graminum) resistance gene Rsg1 in barley. Issue 2 (7th January 2014) - Azhaguvel, Perumal; Mornhinweg, Dolores; Vidya‐Saraswathi, Dhanasekaran; Rudd, Jackie C.; Chekhovskiy, Konstantin; Saha, Malay; Close, Timothy J.; Dahleen, Lynn S.; Weng, Yiqun; Ordon, F.
Abstract The greenbug, Schizaphis graminum (Rondani) is an extremely damaging aphid pest of barley (Hordeum vulgare L.) particularly in the southern Great Plains of the USA. The simply inherited, dominant resistance gene Rsg1 is in all greenbug‐resistant US barley cultivars. In this study, we conducted molecular mapping of Rsg1 using an F2:3 population derived from a cross between the greenbug‐resistant Post 90*4/R015 and susceptible CI2260 inbred lines. Segregation of host responses to greenbug biotype E infestation confirmed that a single dominant gene is responsible for greenbug resistance in Post 90*4/R015. Simple sequence repeat (SSR) markers evenly distributed along the seven barley chromosomes were employed for the construction of a framework genetic map. Linkage analysis placed the Rsg1 locus in the long arm of chromosome 3H (3HL) flanked by SSR markers Bmag0877 and GBM1420 that were 35 cM apart. Polymorphic single‐nucleotide polymorphism (SNP) markers in 3HL were identified from an Illumina GoldenGate SNP assay and used for targeted mapping to locate Rsg1 to an 8.4‐cM interval. Comparative analysis identified syntenic genomic regions in Brachypodium distachyon chromosome 2, in which 37 putative genes were annotated including a NB‐LRR‐type resistance gene homologue that may be a potential candidate gene for the Rsg1 locus of barley. Results from this study offer a starting point for fine mapping and cloning of this aphid resistance gene in barley.